Low-Grade Myofibroblastic Sarcoma of the Acetabulum – A Rare Case with Review of Literature - Sandeep Kumar; Vivek Bhambhu; Shataayu Gugale; Rohit Goyal; Divyank Gupta (Journal of Orthopaedic Case Reports)
Introduction: Low-grade myofibroblastic sarcoma (LGMS) is an atypical and extremely infrequent type of tumor, primary mass being usually present in subcutaneous and soft tissue. Bony involvement is very rare. It has a very high chance of recurrence locally due to its aggressive biological behavior, metastasis in other parts of body is rarely seen. On X-ray, it is visualized as an osteolytic and destructive mass. On magnetic resonance imaging (MRI) this tumor shows heterogenous high signal intensity in T2 images and hypo- to iso-intensity in T1 images. Histologically, these tumors present as diffuse, infiltrative growth pattern traversing between muscle fibers, and cellular atypia with singular mitotic figures. These are obligatory criteria for diagnosis. Due to diagnostic difficulty including histopathological limiting factors, the treatment protocol for LGMS s is still challenging. Case Report: A 21-year-old female with pain in right pelvic and hip region since past 6 months presented with a diffuse swelling over her right hip, along with tenderness over greater trochanter, groin and buttock region. On basis of MRI findings, core needle biopsy was performed for diagnosis and the sample was suggestive of a spindle cell lesion composed of cells arranged in haphazard and vaguely fascicular pattern. To confirm the diagnosis immunohistochemistry marker study was done, revealing features suggestive of LGMS (smooth muscle actin: Positive, B-cell lymphoma 2: Positive, Desmin: Negative, H-caldesmon: Negative). Histomorphological and immune-histo-chemical features showed a final diagnosis of LGMS of right-sided acetabulum. Positron emission tomography -scan was done to rule out any distant metastasis, and it did not show any definitive evidence of abnormal hyper-metabolism elsewhere in the body. Pre-operative computed tomography (CT) angiography was done and plan was made to embolize the feeding vessels preoperatively using the findings of CT angiography. Conclusion: Presentation of LGMS with bone involvement or bone lesions is very rare. Clinicoradiological diagnosis be misinterpreted as a benign lesion which can lead to insufficient resection and local recurrence of the tumor. For treatment in such cases, most studies emphasize on excision of tumor with a wide surgical margin, but regarding the safety distance for better adequacy, relevant data is still inconsistent. In our case, we have reported a case of a 21-year-old female for gross total resection and reconstruction of an acetabular LGMS with extension into iliac wing. To the best of our knowledge, it is the first case of this tumor involving the acetabulum.